A report of the major farm practice in Robina Farms Cebu - Bareja, Mechelin A.; Remandaban, Eleanor T.
This study describes the observed operations management of large scale poultry farms, Robina Farms I (Commercial Layer Farm) and II (Breeder Farm) in Cebu.